SMART SOTONG HOUSE BASED ON IoT TECHNOLOGY IN SITIRIS-TIRIS VILLAGE - Putra, Rio Andika (EINSTEIN (e-Journal), 2024)
Sitiris-Tiris is one of the fishing villages located in Andam Dewi sub-district, Central Tapanuli district, North Sumatra Province. Sitiris-Tiris sea has abundant cuttlefish potential. The abundance of cuttlefish in the Sitiris-Tiris sea is not followed by an increase in fishermen's catches, as experienced by the pamangsih fishing group chaired by Mr Agus Salim Samosir. [RP1] The low catch of cuttlefish obtained by pamangsih fishermen is influenced by weather factors and conventional fishing gear, namely using rabo as a luring tool and fishing rods as fishing gear. Rabo used by pamangsih fishermen is not fully successful because there is no effort to protect the eggs from predatory fish and trawlers who freely pass through the waters. The Student Creativity Programme for the Application of Science and Technology (PKM-PI) organised by the Ministry of Education and Culture was used to create a tool that can catch cuttlefish optimally and can cultivate cuttlefish. The smart cuttlefish house consists of a rabo net tied with a pulley and equipped with a marker lamp to avoid puktrol at night and an IoT (Internet of Things) based image camera connected to a smartphone to monitor cuttlefish. Cuttlefish development can be monitored and harvested by utilising IoT technology so that fishermen can obtain abundant and sustainable catches. Pamangsih fishermen previously only caught 5kg of cuttlefish per day. The smart cuttlefish house designed by the PKM-PI team can catch as much as 10 kg of cuttlefish per day. It is hoped that the smart cuttlefish house made by the PKM-PI team can help fishermen increase cuttlefish catch production and even get to cuttlefish cultivation and can become a pilot project for other cuttlefish fishermen. Translated with DeepL.com (free version)